A global genetic epidemiological review of pseudoexfoliation syndrome - Patrice M. Hicks; Adam Siedlecki; Benjamin Haaland; Leah A. Owen; Elizabeth Au; Michael Feehan; Maureen A. Murtaugh; Sandra Sieminski; Andrew Reynolds; John Lillvis; Margaret M. DeAngelis (Open Exploration Publishing Inc., 2021)
Pseudoexfoliation (PXF) syndrome is an important public health concern requiring individual population level analysis. Disease prevalence differs by geographic location and ethnicity, and has environmental, demographic, genetic, and molecular risk factors have been demonstrated. Epidemiological factors that have been associated with PXF include age, sex, environmental factors, and diet. Genetic and molecular components have also been identified that are associated with PXF. Underserved populations are often understudied within scientific research, including research about eye disease such as PXF, contributing to the persistence of health disparities within these populations. In each population, PXF needs may be different, and by having research that identifies individual population needs about PXF, the resources in that population can be more efficiently utilized. Otherwise, PXF intervention and care management based only on the broadest level of understanding may continue to exacerbate health disparities in populations disproportionally burdened by PXF.